Chemical composition of Egyptian propolis and studying its antimicrobial activity and synergistic action with honey against some multidrug-resistant uropathogens - Asmaa K. Helmy; Nagwa M. Sidkey; Marwa M. Abdel-Aziz; Atef A. El-Hela (Scientific Reports)
Abstract Urinary tract infection (UTI) is one of the most common infections worldwide, increasing the incidence of antibiotic resistance and creating demand for alternative antimicrobial agents. Propolis, a natural antimicrobial agent, has been used in ancient folk medicine. This study evaluates the effectiveness of ethanolic extract of propolis (EEP) alone and in combination with honey against multidrug-resistant (MDR) uropathogens and also investigates the chemical composition of Egyptian propolis, which may be a potential therapeutic approach against MDR uropathogens. EEP was prepared, followed by column chromatographic fractionation using four different solvent systems. The ethyl acetate fraction was further fractionated through vacuum liquid chromatography (VLC). The antimicrobial activity of the EEP, propolis fractions, honey, and EEP-Honey mixture was studied, and the fraction with the best antimicrobial activity was analyzed by GC-MS and HPLC. The results indicated that EEP showed antimicrobial activity against the five MDR uropathogens with varying potential, while honey showed no activity against these pathogens. In comparison, the EEP-Honey mixture exhibited good antimicrobial synergy, with the MIC value decreasing by approximately 4–8 folds. In propolis fractionation, ethyl acetate was the best solvent for extracting antimicrobial substances from EEP, and fraction 5 (F5) was the most active fraction, with inhibition zone diameters of 30.33, 29.00, 21.58, 25.33, and 27.67 mm against MDR P. aeruginosa, E. coli, K. pneumoniae, S. saprophyticus, and C. albicans, respectively. GC-MS analysis of the F5 fraction revealed the presence of phenolics, flavonoids, terpenoids, acids, and alkaloids. In addition, HPLC polyphenol analysis identified 14 phenolic acids and flavonoid compounds with concentrations ranging from 117.36 to 5657.66 µg/g. Overall, the current findings highlighted the promising antimicrobial synergy of the EEP-Honey mixture against MDR urinary pathogens. The phytochemical analysis of propolis also identified potential bioactive compounds responsible for its biological and pharmaceutical properties.